2014
DOI: 10.3389/fmicb.2014.00602
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of arsenite oxidizing bacterial communities in arsenic-rich deltaic aquifers in West Bengal, India

Abstract: High arsenic (As) concentration in groundwater has affected human health, particularly in South-East Asia putting millions of people at risk. Biogeochemical cycling of As carried out by different bacterial groups are suggested to control the As fluxes in aquifers. A functional diversity approach in link with As precipitation was adopted to study bacterial community structures and their variation within the As contaminated Bengal Delta Plain (BDP) aquifers of India. Groundwater samples collected from two shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 69 publications
8
58
0
1
Order By: Relevance
“…It clearly indicated the complex carbon sources of BDP has a role in sustaining and supporting only specific microbial communities. Such natural selection of microbial communities in the BDP groundwaters correlate with increasing As concentration pointing toward the putative role of microbial communities in As mobilization and distribution (Ghosh et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…It clearly indicated the complex carbon sources of BDP has a role in sustaining and supporting only specific microbial communities. Such natural selection of microbial communities in the BDP groundwaters correlate with increasing As concentration pointing toward the putative role of microbial communities in As mobilization and distribution (Ghosh et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…In this study, sediments were collected from two boreholes installed next to the two GSA wells, referred hereafter, as wells 28 (N Ghosh et al, 2014) in Karimpur II block located in Nadia district, West Bengal (Figure 1). Arsenic concentration in these wells ranged from 64 to 131 µg/l and microbial communities in the groundwater were associated with biogeochemical cycling of As and Fe (Ghosh et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the aioA genes have been identified from more than 80 genera of bacteria and archaebacteria, which were isolated from various arsenic-contaminated environments. Most of the aioA genes belong to Alphaproteobacteria, Betaproteobacteria, or Gammaproteobacteria (31)(32)(33)(34)36). However, little is known about the microbial diversity and functional features of AOB from the tailings of a realgar mine that are characteristic of high concentrations of arsenic and sulfate.…”
mentioning
confidence: 99%
“…The aioA gene is usually used as a valuable molecular marker for investigations of the diversity, evolution, and potential activity of AOB (22,29). Recent studies based on metagenomic DNA extracted from soils, sediments, water, minerals, tailings, and geothermal mats with different chemical characteristics and various levels of arsenic contamination suggested that the diversities of AioA proteins differ considerably among these sampling sites (29)(30)(31)(32)(33)(34)(35)(36)(37). Until now, the aioA genes have been identified from more than 80 genera of bacteria and archaebacteria, which were isolated from various arsenic-contaminated environments.…”
mentioning
confidence: 99%